Emerging Technologies, Environment and Research for Sustainable Aquaculture (IntechOpen, 2021)
Traditional aquaculture and fishery systems have caused a series of ecological and environmental problems. For the purpose of sustainable development, new technologies and policies are highly needed in the field of aquaculture and fisheries. This book mainly focuses on two topics, technologies and environment, and sustainable aquaculture. It is expected that this book can help researchers and technicians in the aquaculture industry to get more new ideas and techniques.